Qualidade microbiológica e físico-química de queijo mussarela fatiado à granel e embalado à vácuo - Etges, Joviana Ceolin (2011)
The mozzarella cheese is a product of high consumption, but very susceptible to microbiological contamination. Therefore, this study aimed to evaluate the microbiological and physical-chemistry of sliced mozzarella cheese in bulk and vacuum-packed, sold in supermarkets in the Northwest region of Rio Grande do Sul State. We evaluated five marks (50 samples) of vacuum-packed mozzarella cheese (A, B, C, D and E) and a mark (25 samples) sold in bulk (F). Microbiological tests were performed according to Normative Instruction 62, August 26th, 2003: fecal coliform counts (45ºC), Salmonella sp. and coagulase positive Staphylococcus in two different periods during the validity period (period I) and after the expiration of the samples (period II). Were also conducted analysis of pH, fat and moisture, according to the Normative Instruction 68, December 12th, 2006. The physicochemical parameters classified the samples as fat cheese and medium humidity and all attended the legal parameters established by the Brazilian legislation. The microbiological results showed that all samples were within the standards for fecal coliform and coagulase positive Staphylococcus in both periods of analysis. However, in period I detected the presence of Salmonella sp. in one of the marks (16.67 %), being improper for human consumption.